Anodized Aluminum Oxide/Polydimethylsiloxane Hybrid Mold for Roll‐to‐Roll Nanoimprinting. (16th April 2018) - Kim, Sanghoon; Hyun, Seung; Lee, Jaeyong; Lee, Kyu Seong; Lee, Woo; Kim, Jin Kon
Abstract: Two types (hard and soft) of the molds are widely used in nanoimprint lithography for a high throughput over a large area, and high‐resolution parallel patterning. Although hard molds have proven excellent resolutions and can be used at high temperatures, cracks often occur in the mold in addition to the requirement of high imprinting pressure. On the other hand, though soft molds can operate at lower pressures, they give poor pattern resolution. Here, a novel hybrid mold of anodized aluminum oxide (AAO) template attached to a flexible polydimethylsiloxane (PDMS) plate is introduced. Due to the flexible nature of PDMS, various polymer nanostructures are obtained on flat and curved substrates without crack formation on the AAO mold surface. Furthermore, the hybrid mold is successfully used for roll‐to‐roll imprinting for the fabrication of high density array of various shaped polymeric nanostructures over a large area. Abstract : A novel hybrid mold of an anodized aluminum oxide (AAO) template with various pore sizes and shapes chemically attached to a flexible poly(dimethylsiloxane) (PDMS) plate is prepared. Through roll‐to‐roll nanoimprinting using the AAO/PDMS hybrid mold, a high density array of polymeric nanostructures is successfully fabricated on a flexible substrate (poly(ethylene terephthalate)) over a large area without cracks on the AAO template.